A Study of the Effect of Temperature on the Structural Properties of Zinc Oxide (ZnO) Thin Films - Fadel Ezzdin El-Sharif; Abu Al-Qasim Masoud Al-Qat; Asmaa Issa Moawi (Libyan Journal of Medical and Applied Sciences, 2025)
Zinc oxide thin film technology is a leading technology in many advanced industries, due to its high efficiency in the manufacture of electrical and electronic devices, and its highly effective physical properties. The study of the effect of temperature on revealed that the pure zinc oxide film had a close-packed hexagonal structure. When measuring the crystal size of the zinc oxide films, it was found that it had different spectral values due to heat treatment at 80°C. This is due to the appearance of a network on the film surface. This type of film formation produces high-quality films. Electron microscopy examination revealed the appearance of defects in the film material, which affected the physical and chemical properties of the deposited films. Measurements showed that the average thickness of the deposited films was between 14.26 μm and 18.68 μm at two temperatures (70°C and 80°C). The results were in good agreement with published results.